Gold nanostar-mediated neural activity control using plasmonic photothermal effects. (January 2018) - Lee, Jee Woong; Jung, Hyunjun; Cho, Hui Hun; Lee, Jung Heon; Nam, Yoonkey
Abstract: Nanomaterials have emerged as an essential tool for the understanding of cellular level mechanism in the fields of biology and medical science. Recently, researchers have been studying the regulation of neuronal activity using plasmonic nanoparticles and light, and it has been reported that photothermal effects could lead to both excitation and inhibition of neuronal cells. So far, only a few photothermal transducers have been applied to modulate neural activity. In this paper, we synthesized biocompatible gold nanostars (AuNSs) which generate heat by absorbing near-infrared (NIR) light. And we used the AuNS to inhibit the activity of neurons through light stimulation. We have demonstrated that AuNS inhibits the neural activity by NIR laser in both chip-attached mode and cell-attached mode. We also confirmed the suppression of single neuron signal by using digital micromirror device (DMD) set up. This approach is possible to inhibit the neural firing by controlling the intensity of light, and overcome the disadvantages of conventional electrochemical stimulation methods. This method of NIR-mediated stimulating neurons using light sensitive AuNS will be a powerful tool for neuromodulation researches and neuroscience studies.